2012 Review of Data Provision to the Fund for Surveillance Purposes. (Policy Papers; Policy Paper ;, 2012)
The IMF keeps data provision by members under periodic review since timely, accurate, and comprehensive data are essential for fulfilling its surveillance mandate. The previous Review of Data Provision to the Fund for Surveillance Purposes was discussed by the Executive Board in March 2008 (the 2008 Review). The 2008 Review introduced a new classification system for rating the adequacy of data provision by a member to help with this assessment. The present review was expected to be conducted in 2013, but was brought forward to 2012 in the context of the ongoing global crisis. In particular, the Managing Director's (MD) statement on the 2011 Triennial Surveillance Review (TSR) announced that the Review of Data Provision to the Fund for Surveillance Purposes would be brought forward to 2012 to allow the Board to consider where more and better data could be leveraged to enhance surveillance.